Synthesis and Physico-Chemical Properties of Homoleptic Copper(I) Complexes with Asymmetric Ligands as a DSSC Dye - Tomohiko Inomata (MDPI AG, 2021)
To develop low-cost and efficient dye-sensitized solar cells (DSSCs), we designed and prepared three homoleptic Cu(I) complexes with asymmetric ligands, M1, M2, and Y3, which have the advantages of heteroleptic-type complexes and compensate for their synthetic challenges. The three copper(I) complexes were characterized by elemental analysis, UV-vis absorption spectroscopy, and electrochemical measurements. Their absorption spectra and orbital energies were evaluated and are discussed in the context of TD-DFT calculations. The complexes have high VOC values (0.48, 0.60, and 0.66 V for M1, M2, and Y3, respectively) which are similar to previously reported copper(I) dyes with symmetric ligands, although their energy conversion efficiencies are relatively low (0.17, 0.64, and 2.66%, respectively).